ТЕАТРАЛЬНІСТЬ СУЧАСНИХ МУЗЕЙНИХ КОМУНІКАЦІЙ: СОЦІАЛЬНО-ФІЛОСОФСЬКИЙ АСПЕКТ - Прокопович Л. В., (International Journal of Innovative Technologies in Social Science, 2019)
The purpose of the study is to identify and comprehend the socio- philosophical foundations of the theatricality of modern museum communications. The methodological research strategy is based on the concept of theatricality of sociocommunicative manifestations of culture (using the methodological apparatus of sociocultural analysis). This approach made it possible to find out that the museum space is communicative in its goals, objectives and forms of existence. This space is not closed, because museum communication is not only the exchange of information within the museum. The exit of museum communication into social reality is facilitated by the theftricalization of museum space and the formation of on appropriate information and semantic field (environment) using works of fiction.